(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the issues of improving the emergency forecasting system. The analysis of man-made emergencies in recent years in the Republic of Uzbekistan, as well as legislative acts in the direction of monitoring emergencies. The directions for the development of this area are proposed, in particular, the creation of a data center with an algorithm for assessing the necessary data with the subsequent application of risk identification indicators is proposed.